2016
DOI: 10.1111/1751-2980.12408
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as biomarkers and regulators of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a complicated disease affected by the interaction of environmental and genetic factors; however, the precise pathogenesis of the disease has not been fully determined. There is a need to better understand the pathogenesis of NAFLD and to identify non-invasive diagnostic modalities. Recent advances in systematic biology and epigenetics have improved our understanding of the genotype-phenotype relationships in NAFLD. MicroRNAs (miRNAs) are important regulators of a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 80 publications
(178 reference statements)
0
21
0
Order By: Relevance
“…(7) It has been reported that miRs regulate lipid metabolism, inflammation, and fibrosis in NAFLD through the posttranscriptional silencing of the target genes by base-pairing to partially complementary sites in the 3′-untranslated region (UTR) of target mRNA. (8) The miR-192-5p is one of the most abundant miRNAs in liver tissue. (9) Research suggests that serum miR-192-5p levels can be used as a potential biomarker for disease progression of NAFLD.…”
Section: Approach and Resultsmentioning
confidence: 99%
“…(7) It has been reported that miRs regulate lipid metabolism, inflammation, and fibrosis in NAFLD through the posttranscriptional silencing of the target genes by base-pairing to partially complementary sites in the 3′-untranslated region (UTR) of target mRNA. (8) The miR-192-5p is one of the most abundant miRNAs in liver tissue. (9) Research suggests that serum miR-192-5p levels can be used as a potential biomarker for disease progression of NAFLD.…”
Section: Approach and Resultsmentioning
confidence: 99%
“…Similarly, a recent study reported that miRNA-34a had moderate accuracy for distinguishing between NASH and NAFL (AUROC=0.78) [44]. Our study involved a total of 14 miRNAs, which have several roles in the pathogenesis of NAFLD [14,45], such as, lipid synthesis (miRNA-122), fatty acid b-oxidation (miRNA-34a, -122), endoplasmic reticulum stress (miRNA-30, -34a, -122), in ammation (miRNA-34a, -99a, -146b), brosis (miRNA-122), tumorigenesis (miRNA-99a), and cell autophagy and apoptosis (miRNA-34a). The relationships between miRNAs and NASH pathogenesis can be both one-to-many and many-to-one.…”
Section: Discussionmentioning
confidence: 71%
“…In brief, miRNAs can suppress or promote expression of target genes [41]. miRNAs widely participate in multiple pathological processes of NAFLD [14,41], and their serum levels differ signi cantly between healthy individuals and NAFLD patients. Hence, they have become a new potential non-invasive biomarker for diagnosis of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs are small, non‐coding RNAs which regulate the expression of numerous target genes at both transcriptional and translational levels. Altered microRNA profiles have been found in liver injury in both human and experimental animal models . MicroRNA‐122 (miR‐122), the most abundant microRNA in the liver, constitutes about 70% of all microRNAs in mature hepatocytes, and decreased levels of hepatic miR‐122 has been found from patients as well as animals with ALD/NASH .…”
Section: Introductionmentioning
confidence: 99%